Challenges and perspectives of movement ecology research in Brazil - Alves-Eigenheer, Milene Amâncio [UNESP]; Niebuhr, Bernardo Brandão [UNESP]; de Faria Oshima, Julia Emi [UNESP]; Kanda, Claudia Zukeran [UNESP]; Ramos, Danielle Christine Tenório Leal [UNESP]; Da Silveira, Natália Stefanini [UNESP]; Honda, Laura Kyoko [UNESP]; Kerches-Rogeri, Patrícia [UNESP]; de Souza Salzano, Lígia Pereira [UNESP]; Moraes, André Luiz Bitencourt [UNESP]; Mokross, Karl Stephan [UNESP]; Ribeiro, Milton Cezar [UNESP] (Asociacion Espanola de Ecologia Terrestre (AEET), 2023)
Challenges and perspectives of movement ecology research in Brazil. The recent progress in movement ecology research was driven by technological advances that facilitated the quantification and analysis of fine scale movement. Here we review and comprehensively describe scientific research on movement ecology in Brazil, its main topics, challenges and perspectives. To assess it, we performed a literature survey of movement ecology in Brazil and analyzed responses of a questionnaire completed by attendees that took place at the I Movement Ecology Brazil Workshop, in 2015. We describe the most studied taxa, topics of research and technologies, the most studied biomes, and the greatest challenges faced by Brazilian scientists. We propose collaborations among different lines of study and interdisciplinary research centers, besides recommending more education beyond the technical aspects of this research field, towards the development of competent and well-rounded scientists. Access to technology without bureaucracy, the growth of Brazilian tracking equipment companies, enhancement of national and international research networks and partnerships among biological and statistical sciences are some factors that will shape the autonomy of Brazilian researchers working in movement ecology. Our main suggestion for future directions is to integrate biomechanical, cognitive and optimality paradigms with movement-related ecological processes such as predation and seed dispersal, and the unique biodiversity and fieldwork context found in Brazil..
Keywords: animal movement; GPS collar; movement analysis; radiotelemetry